Upgrading and Repairing Networks, Fourth Edition - Ogletree, Terry William (Que, 2011)
Even if you aren't a networking professional, Upgrading and Repairing Networks explains those tough networking concepts in a way that won't make you reach for a bottle of aspirin, starting with the fundamentals and working through more advanced concepts. Now in its fourth edition, this industry classic networking reference gives you real world, in-depth explanations of confusing networking architectures and protocols, and helps you track down and repair networking problems that are costing you and/or your company money - right now. Don't be the only networking professional caught in a network meltdown without a copy of this trusty tome at your side.